A comparative study of secondary mathematics curricula of Turkey, Estonia, Canada, and Singapore - Fatma Serçe; Filiz Acar (Journal of Pedagogical Research, 2021)
This study aims to reveal the similarities and differences in the secondary mathematics curriculums (SMC) of Turkey, Estonia, Canada, and Singapore during the 2018-2019 academic years by comparing them in terms of the curriculum components. In this context, the horizontal approach technique, one of the comparative education approaches, was used in the study. The study is qualitative research and was carried out through document analysis in collecting data. Secondary mathematics curricula of each country were subjected to content analysis using NVivo 10 qualitative analysis program. Curricula were examined in terms of general characteristics, objectives, content, learning-teaching process, assessment, and teacher's duties and responsibilities dimensions, and comparisons between countries were made. The results revealed that the majority of the learning outcomes in the SMC of Turkey and Estonia are in the knowing cognitive domain while applying is dominant in Canada and reasoning in Singapore SMCs. In addition, the SMC of Singapore provided the most detailed information regarding the assessment. Besides that, the SMC of Singapore was the curriculum that most comprehensively reflects the teacher's duties and responsibilities towards curriculum, teaching and learning process, and evaluation process.